Efficient selective hydrolysis of terephthalonitrile to 4-cyanobenzoic acid catalyzed by a novel nitrilase from Pantoea sp. (December 2018) - Zhang, Mujiao; Yao, Peiyuan; Yu, Shanshan; Zhang, Tongcun; Wu, Qiaqing; Zhu, Dunming
Graphical abstract: Highlights: A nitrilase from Pantoea sp. catalyzes the selective hydrolysis of terephthalonitrile to 4-cyanobenzoic acid. The transformation achieved much higher substrate concentration (100 g/L), yield (91%) and productivity (26.13 g/(L h)). The nitrilase catalyzes the hydrolysis of various aromatic nitriles and aliphatic nitriles. An industrially feasible enzymatic method for the synthesis of 4-cyanobenzoic acid was developed. Abstract: An efficient method for the production of 4-cyanobenzoic acid from terephthalonitrile was developed by using a novel nitrilase from Pantoea sp. AS-PWVM4 (PaNIT). Under the optimized reaction conditions (pH 8.0 and 37 °C), up to 100 g/L substrate concentration was almost completely converted to 4-cyanobenzoic acid with wet whole cells loading of 5.0 wt% in 4 h and the isolated yield was 91%. The substrate concentration, yield and productivity (26.13 g/(L h)) are much higher than those in the previous studies. Furthermore, PaNIT has broad substrate specificity of catalyzing the hydrolysis of various aromatic nitriles and aliphatic nitriles. These results suggest that PaNIT is a valuable nitrilase with potential practical applications.